P070 'ChemSex' within men who have sex with men (MSM): How big is the problem outside major conurbations?. (30th June 2016) - Wiggins, Helen; Mebrahtu, Helen; Sullivan, Ann; Field, Nigel; Hughes, Gwenda
Abstract : Background/introduction: Sexualised substance use (chemsex) amongst men who have sex with men is well documented in some areas (London, Brighton, Manchester), and associated with high-risk sexual practices and acquisition of sexually transmitted infections. Aim(s)/objectives: To explore demand for chemsex services in UK GUM clinics, including outside major conurbations Methods: An online survey was distributed to clinical staff in GUM clinics across the UK. Analysis at clinic level was undertaken for England, with clinics split into 4 categories: (A) urban conurbation, (B) urban with city/town, (C) urban with significant rural, and (D) non-urban. Results: 357 individuals responded from 152 clinics, 90% were from England. Country–specific clinic response rates were 63% (135/214) in England, 80% (4/5) Northern Ireland (NI), 8% (3/39) Scotland and 83% (10/12) Wales. 82% (227/278) of respondents reported seeing patients who disclosed chemsex (82% England (205/251), 83% NI (5/6), 75% Scotland (6/8), 85% Wales (11/13)), and there was broad consensus that chemsex services (86%) and training were needed (98%). 64% (68/106) of clinics reported routinely asking selected patients about chemsex, 10% (11/106) asked all patients, and the remainder did not ask. Although the proportion of clinics seeing chemsex and the frequency of chemsex consultations was reported to be higher in more urban settings, differences were not significant and many clinics in rural areas reported chemsex consultations (Table 1). Discussion/conclusion: Chemsex consultations occur in most GUM clinics across the UK albeit to varying degrees. These data suggest a widespread need for specialist chemsex services and training.